Implementasi Islam dan Hak Asasi Manusia dalam Perspektif Al-Qur’an dan Hadits: Studi di SMA Syekh Abdul Qodir Al Jailani Rangkang Probolinggo - Begi Muhammad; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the implementation of Islamic values and human rights (HR) at SMA Syekh Abdul Qodir Al Jailani Rangkang Probolinggo, based on the perspectives of the Qur’an and Hadith. The primary focus of this research is to identify how Islamic teachings, emphasizing justice, tolerance, and respect for individual rights, are applied in the educational environment. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The findings reveal that SMA Syekh Abdul Qodir Al Jailani successfully implements Islamic principles in its curriculum to instill awareness of the importance of respecting diversity, upholding justice, and protecting human rights. The school environment is designed to support inclusivity, where every student feels accepted without discrimination. These Islamic values are realized through learning programs, extracurricular activities, and student character development. Teachers play a central role as role models in teaching and practicing the values of justice and tolerance. The conclusion of this study is that SMA Syekh Abdul Qodir Al Jailani has successfully integrated Islamic teachings with human rights principles, creating a generation that is not only religious but also socially aware. This study provides significant contributions to understanding the relevance of the Qur’an and Hadith in the context of modern education and human rights.